The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1445-6664.2011.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Purple witchweed (Striga hermonthica) germination and seedbank depletion under different crops, fallow, and bare soil

Abstract: Seedbank density is an important aspect that determines the amount of damage that the parasitic weed, purple witchweed (Striga hermonthica; hereafter, called "Striga"), causes on its crop hosts.The seedbank depletion of Striga was measured in Mali and Niger during the 2004 rainy season under the host crops, pearl millet and sorghum, the non-host crops, cowpea and sesame, the intercrops of pearl millet or sorghum with cowpea or sesame, and fallow with or without weeding. Two methods were used and compared; name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The overall conclusion is justified that the proof of principle using the suicidal germination approach in the field is a great step forward in the control of parasitic weeds and can probably be combined with other known methods for seed bank depletion . Further research efforts in the area of SLs will contribute to the discovery of new avenues for their practical application .…”
Section: Parasitic Weed Control Using the Suicidal Germination Approachmentioning
confidence: 89%
“…The overall conclusion is justified that the proof of principle using the suicidal germination approach in the field is a great step forward in the control of parasitic weeds and can probably be combined with other known methods for seed bank depletion . Further research efforts in the area of SLs will contribute to the discovery of new avenues for their practical application .…”
Section: Parasitic Weed Control Using the Suicidal Germination Approachmentioning
confidence: 89%
“…These free fatty acids and amylose form complex, and the complex molecules become spiral-like and dense crystallization, which limits the expansion of starch during cooking, makes rice hard and sticky, and affects the gelatinization of starch. Degreasing had little effect on cooking hardness and viscosity of rice after aging, but it had effects on the viscosity curve of rice flour paste, which decreased its viscosity value, refrigeration recovery value and maximum viscosity value (Tsai et al, 2012;Wiset et al, 2011). The experimental results showed that there was no obvious aging phenomenon after cooking rice treated with n-hexane and stored at 4~25 °C without lipids (Shu et al, 2014;Coudert et al, 2015).…”
Section: Effects Of Rice Aging On Physicochemical Properties Of Lipidsmentioning
confidence: 95%
“…These objectives are mutually dependent. The seed bank can only be reduced when new seed inputs are smaller than the output caused by unsuccessful germination, pathogens, seed predation or natural death of the seed (Lonsdale 1993;Westerman et al 2003;Grundy et al 2003;van Mourik et al 2005van Mourik et al , 2011. Reduction of the parasite reproduction and increase of seed bank demise while preventing seed dispersal to other places can all be achieved by cultural measures.…”
Section: Seed Bank Controlmentioning
confidence: 98%
“…Recently, van Mourik et al (2011) compared Striga hermonthica seed bank depletion rates, attained under bare or weedy fallow and mono-or intercropping with a non-host crop, to the rates attained under cereal (sorghum or millet) monocropping. They found that seasonal depletion rates of the soil seed bank under continuous mono-cropping of the host crop (75-82 % under sorghum depending on variety and 74 % under millet) were higher than when intercropped with a non-host crop (49-66 %), which in turn depleted the soil seed bank more than when the non-host crop was grown as mono-crop (35-43 %) or when the soil was under a weedy fallow (47 %) or left bare (28-43 %).…”
Section: Cropping Systemsmentioning
confidence: 99%